DOING GERMAN DIFFERENTLY: NEW RESEARCH PRACTICES AND PARTNERSHIPS AROUND THE UK. (7th June 2018) - Braun, Rebecca; Schofield, Benedict
ABSTRACT: This article profiles six current projects in UK German Studies, as first presented by Rebecca Braun, Katrin Kohl, Laura Bradley, James Hodkinson, Seán Williams, and Benedict Schofield at the meeting of the Association for German Studies in September 2017. The projects combine ʻcoreʼ Modern Languages skills (close‐textual analysis, cultural analysis, linguistic and cultural translation) with 'outlier' methods that emerge and are developed when engaging with a range of stakeholders beyond the discipline and beyond academe. Collectively, the contributions provide insight into how to set about conceptualising and justifying this sort of work, and reflect on how it might enable us to look at the scope and purpose of German Studies in a new light.